(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Throughout the history of mankind, the development of religion and the issue of medicine have gone through the stage of growth in mutual noumenal harmony. In particular, whether it is based on religion or contradicts religious teachings was in the center of discussion. Although religious motifs are not found in the medical works written by ancient scientists, the issue of medicine is always explained in religious literature. Later, with the strengthening of the role of religion in society, medical scientists also tried to prove their views with religion. At the same time, the monks themselves worked as healers. In Christianity, this is evidenced by the miracle given to Jesus (a.s.) and his healing of people, healing the eyes of the blind, cleaning the skin of lepers, and stroking the paralyzed. After the ascension of Jesus (a.s.) from the earth, the apostles, and after them the saints, undertook this task. After all, according to the Christian faith, the disease is caused by sin, and its healing is through repentance and spiritual purification. In our opinion, this issue creates the need to study the field of medicine in religious teachings, sources and ages.